Miejsce wrocławskiego obszaru metropolitalnego w systemie osadniczym regionu - Miszczak, Katarzyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The main aim of this article is to show the position of Wroclaw metropolitan area in settling system of region. The article presents important features of Wroclaw agglomeration, describe changes in this area and similarity measures between Wroclaw city and subregions of Lower-Silesian Province. The structure of employment in Wroclaw was also researched in individual years.Based on the research carried out and the conclusions drawn, the author states that using new external condition, connected first of all with the European integration process and internal ones determined by forming only in Wroclaw metropolitan area net structure, but what is the most important showing egsogenous features is undoubtedly it a huge chance for decision-makers and inhabitants of this part of Poland. The ventures which are undertaken in this area and realized in an optimal manner should affect the modernization of social and economic structure of whole Lower Silesia and contribute to increasing of this region's competitive power.Because of the article's limited volume, presented matters, opinions and conclusions were depicted in a synthetic form. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1087, s. 100-110